Vatican from Utrecht to Rastatt, from Perspective of Christian Cole, Representative of England in Venice - Kocić, Marija V. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
This work analazyses the opinion of Vatican and Pope Clement XI (1700–1721) about new relations in Italy, that are consequnces of Rastatt and Utrecht treaties. Archive materials from the National Archives in London, specifically reports of an England's representative in Venice were used. Since he regularly received reports from Rome, Naples and Sicily, Christian Cole regularly and dutifully infomed London of occurences in these states. Due to the mentioned fact, his correspondence provides a certain overview of events in Vatican, and some dispositions are opposed to those revealed by the historiography of this period. The Utrecht Peace caused significant changes in the Apennine Peninsula, and Vatican was not prepared to accept them. Breakthrough of Austria into this part of Europe is, by all means, one of its most important consequences. One of pontiff's responses to changes on the political map of Italy was his approaching to Charles VI, whom he saw as a protector of the Catholic Church, in the period when the conflict with Louis XIV culminated because of his efforts to achieve autonomy for the Gallican church. After Rastatt, the Pope became deeply disappointed with Charles VI. This was bound to happen, since Charles VI tried to introduce the Kingdom of Naples into his sphere of interest, which was in conflict with Vatican's interest, and the approaching noticed during 1713 could not last for long, in the circumstances when the Pope had to fight for his endangered privileges.
Keywords: Peace of Utrecht; Napoly; Sicily; Carlo VI; Christian Cole; Clement XI; Papal state (Vatican)